Estonia : A Successfully Integrated Population-Registration and Identity Management System - Aguilar Rivera, Ana Milena (World Bank, Washington, DC, 2017)
Integrated civil registration and vital statistics (CRVS) and identity management systems (IDMS) provide a critical basis for identity management and the establishment of personal identity. When developed in an integrated matter, these systems can provide major savings in terms of time and costs, in addition to creating efficiencies in the flow of information across relevant institutions. Some countries are leading the development of more integrated approaches, and the lessons learned, if properly documented, may be useful to many low- and middle-income countries. This report describes the particular case of Estonia, and the process through which the country has developed an integrated population registration and identification system aiming at improve public service delivery. The report identifies enabling factors and best practices that may be applicable to other countries.